Pomen patentov v družbi znanja: socioekonomske implikacije za podjetja in družbo - Ilič, Branko (Teorija in praksa, 2006)
The article deals with the socio-economic role of patent as the intellectual property right granted to stimulate knowledge creation and innovation as well as innovation competition in a knowledge-based society. Deriving from the patent law the three economic arguments are analysed as opposed to the traditional and in favour of the alternative competitive economic theory of patents. The fundamental message of the latter is that the patent does not preserve free use of disclosed invented knowledge as an input for R&D of competitive innovations. Following the cumulative causation hypothesis some socio-economic implications of patent are exposed also for firm competitiveness or competitive advantage (e.g. knowledge strategies, HRM practices), value creation, as well as for social welfare and inequality in knowledge societies or knowledge-based economies.
Keywords: Patenti; Patents; Innovations; Inovacije; Knowledge; Znanje; Človeški kapital; Human capital; Research works; Raziskave; Razvoj; Development; Competitiveness; Konkurenčnost; družba znanja